2016
DOI: 10.1088/2043-6262/7/1/015004
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoplates surfaced-decorated by WO 3 nanorods for NH 3 gas sensing application

Abstract: Zinc oxide (ZnO) nanoplates and tungsten trioxide (WO3) nanorods were synthesized by hydrothermal treatment from zinc nitrate/potassium hydroxide and sodium tungstate/hydrochloric acid, respectively. The structure, morphology and compositions of the as-prepared WO3/ZnO nano-composites were characterized by x-ray diffraction, field emission scanning electron microscopy and energy dispersive spectroscopy. The obtained ZnO nanoplates have regular shape, single-crystal wurtzite structure with the thickness of 40 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…They suggested that the mesoporous structure allows for fast diffusion of gas molecules, resulting in high rates of gas adsorption and desorption. Nguyen et al [87], by a hydrothermal method, synthesized ZnO nanoplates made of single-crystal wurtzite structure with a thickness of 40 nm and 200 nm × 400 nm in lateral dimensions. The authors also prepared composites by mixing the synthesized ZnO nanoplates and WO 3 nanorods with different weight ratio.…”
Section: Ammoniamentioning
confidence: 99%
“…They suggested that the mesoporous structure allows for fast diffusion of gas molecules, resulting in high rates of gas adsorption and desorption. Nguyen et al [87], by a hydrothermal method, synthesized ZnO nanoplates made of single-crystal wurtzite structure with a thickness of 40 nm and 200 nm × 400 nm in lateral dimensions. The authors also prepared composites by mixing the synthesized ZnO nanoplates and WO 3 nanorods with different weight ratio.…”
Section: Ammoniamentioning
confidence: 99%
“…The procedure has been reported in ref. [15]. The crystal structure of ZnO nanoplates was identified using Bruker-AXS (Siemens) D5005 with CuKα radiation (λ = 1.54065 Å) at a scanning rate of 0.03 • /2 s within the 2θ range of 30-70 • .…”
Section: Methodsmentioning
confidence: 99%
“…These studies were conducted at room temperature. A recent study reported the influence of UV light combined with thermal energy on sensing materials [13][14][15]. However, research on this field is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The massive researches showed that ZnO had the faster response and recovery time, higher sensitivity toward NO x gas, and the study on ZnO‐based gas sensors attracted the researchers largely. Hitherto, the researchers have synthesized ZnO with different morphology, including nanorods, nanosheets, nanotubes, nanoparticles, nanoplates, nanofilms, and so forth . The different morphology has the considerable impact on the gas sensing performance of MOS gas sensors.…”
Section: Introductionmentioning
confidence: 99%